Pattern of drug-induced bleeding in a tertiary care hospital - Negi, Rajinder; Kashyap, Rajesh; Prashar, Anupam; Sharma, Brij; Asotra, Sanjeev; Gupta, Dilip (International Journal of Research in Medical Sciences, 2017)
Background: It is a well-known fact that drug-induced bleeding causes considerable morbidity and mortality. Drugs that induce bleeding do so by aﬀecting either anti-platelet Function and /or coagulation. By the frequency of their use, anti-platelet, a coagulant, thrombolytic and NSAIDs are the most commonly implicated drugs. Upper gastrointestinal bleeding is commonest adverse drug reaction associated with hospital admission. Signiﬁcant number of these could be prevented if simple guidelines are followed. Spontaneous cessation of bleeding occurs in as many as 85% of cases. Early intervention is required in those if bleeding does not stop spontaneously. Objective of the study was to determine the pattern of drug induced bleeding in tertiary care hospital setting. Methods: It was a hospital based observational study conducted during one year study dura on ((June 1, 2014 to May 31, 2015) amongst all adult patients admitted to the hospital with drug induced bleeding. Statistical analysis was done by frequency measurement for categorical variables. Chi- square test was used to determine associations. A p-value of<0.05 was taken as statistically signiﬁcant. Results: A total number of 110 cases with history of bleeding were enrolled. Commonest drug that caused bleeding was a platelet with 29 (26%) cases followed by combination of 2 or more drugs in 25 (23%) cases, then NSAIDs and anticoagulants in 24 (21%) and 23 (20%) cases respectively. Upper gastrointestinal bleeding was the commonest site of bleeding seen in 64 (58%) cases. The commonest drugs causing upper GI bleeding were NSAIDs seen in 24 (37.5%) cases followed by a platelet 22 (34.3%), combined drugs in 09 (14%) cases. (P<0.001) In overall severity most cases of drug induced bleeding had mild bleeding with 61 cases as compared to 38 cases of moderate and 11 cases of severe bleeding. There were signiﬁcantly higher proportion of mild and moderate bleeding in upper gastrointestinal bleed cases in comparison to other sites of drug induced bleeding in this study (p<0.01). 7 (6.4%) out of 110 patients died and 103 (93.6%) patients recovered and were discharged. Conclusions: Clinical management of bleeds requires careful assessment of the patient, haemodynamic stabilisation, discontinuation of the offending medication and, where appropriate, reversal of the haemorrhagic effects and specific therapies such as endoscopic haemostatic therapy.